Examining mindfulness-based training effects upon uncertainty reduction in initial interaction between strangers - Whitt, Joseph M., author; Crowley, John, advisor; Aoki, Eric, committee member; Rickard, Kathryn, committee member (Colorado State University. Libraries, 2015)
This research project is meant to supplement the extant literature on initial interaction between strangers. The central inquiries of this study examine whether individuals can reduce relational automaticity found in initial interactions and, in turn, embody more openness toward strangers. The study investigates the growing field of mindfulness practice, known for reducing behavioral automaticity and boosting pro-social effects, and determines how it impacts the relational outcomes in initial interaction. To accomplish this, it compares the performance of two experimental groups in initial interaction, one group that is exposed to a mindfulness treatment and one control. By analyzing the participants' uncertainty reduction strategies, this research aims to determine whether mindfulness plays a moderating role for uncertainty reduction in initial interaction.
Keywords: initial interaction; strangers; uncertainty reduction theory; mindfulness; homophily; uncertainty